The Family Crisis Behind Democracy: An Analysis of Family Resilience of 2024 General Election Organizers in North Lombok Regency - Putri, Suci Ramadhani; Anam, Ahmad Gautsul; Nizamudin, Nizamudin (POLITEA, 2025)
This study aims to examine the forms of crisis experienced by the families of General Election organizers in North Lombok and examine their family resilience, efforts to negotiate roles amidst the demands of public and domestic spaces. This research is a qualitative study that uses an ethnographic approach. The data analysis of this research uses a stepwise forward method. The primary data source of this research is the travel experience of the General Election organizers and their families during the stages of the Regional Head Election in North Lombok. Secondary data are literature, documents, journals relevant to this research. Data collection was conducted using interview, observation and documentation techniques. The results of this study found that Election Organizers in North Lombok experienced a family crisis due to the demands of the domestic space and family space. The crisis faced by female organizers tends to be more complex than male organizers. In facing the crisis, some families are resilient, while others end up not resilient. This research argues that democracy will not run healthily if the actors of democracy, namely Election Organizers, experience a family crisis. Therefore, family resilience is an important foundation for the quality of democracy itself.